Pemimpin Ideal Perspektif Hadis: Refleksi Menyongsong Pemilihan Umum Tahun 2024 - Hendro, Beko; Indanu, Rahmat Agum; Tauhid, Muhammad (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2023)
AbstractThis research examines the criteria for leaders from a hadith perspective, especially in facing the 2024 general election. This paper aims to examine the meaning and criteria for leaders found in hadith sources. This research is the result of library research using qualitative methods. The data used consists of primary sources in the form of various hadith books which discuss the criteria for leaders, as well as secondary sources in the form of books, articles, journals and other references relevant to the discussion theme. The data analysis method used is descriptive analytical. This article explains the political and electoral system in Indonesia, including the challenges and polemics that often arise, such as the quality of leadership and political polarization. This research found seven prophetic characteristics that leaders must have, namely: being religious and understanding religious values, having knowledge and managerial knowledge, acting fairly in leadership, being able to carry out and fulfilling the mandate given, having integrity and honesty, having a responsible attitude and understand that everyone is responsible to Allah and the society they lead and has experience, spiritual maturity, maturity and wisdom even though they are still young. Keywords: Leader Criteria, 2024 Election, Fairness, Trustworthiness, Experience, Responsibility.Abstrak:Penelitian ini mengkaji tentang kriteria pemimpin perspektif hadis, terutama dalam menghadapi pemilihan umum tahun 2024. Tulisan ini bertujuan untuk mengkaji makna dan kriteria pemimpin yang terdapat dalam sumber-sumber hadis. Penelitian ini merupakan hasil dari penelitian kepustakaan dengan metode kualitatif. Data yang digunakan terdiri dari sumber primer berupa berbagai kitab hadis yang membahas tentang kriteria pemimpin, serta sumber sekunder berupa buku, artikel, jurnal dan referensi lain yang relevan dengan tema pembahasan. Metode analisis data yang digunakan adalah deskriptif analitis. Artikel ini menjelaskan sistem politik dan pemilu di Indonesia, termasuk tantangan dan polemik yang sering muncul, seperti kualitas kepemimpinan dan polarisasi politik. Penelitian ini menemukan tujuh katakter sifat-sifat profetik yang harus dimiliki pemimpin yaitu: beragama dan memahami nilai-nilai agama, memiliki ilmu pengetahuan dan manajerial, berlaku adil dalam kepemimpinan, mampu menjalankan dan menunaikan amanah yang diberikan, berintegritas dan jujur, memiliki sikap bertanggungnjawab dan memahami bahwa semua ada perbertanggungjawabnya kepada Allah dan masyarakat yang dipimpinnya serta memiliki pengalaman, kematangan spiritual, kedewasaan dan kebijaksanaan walau masih dalam usia muda.  Kata Kunci: Kriteria Pemimpin, Pemilu 2024, Adil, Amanah, Pengalama, Tanggung jawab.